Nutritional contribution of oral nutrition formulas in dialysis patients - Soto, Danery L. (2023)
In patients undergoing dialysis, malnutrition is a very frequent characteristic, which is why oral nutritional supplementation administered to these patients can contribute to adequate protein intake and energy intake, thus improving protein anabolism. The objective of the present review was oriented to the bibliographic search of existing scientific articles on the nutritional contribution based on artificial enteral nutrition in patients with chronic renal disease submitted to dialysis which tends to increase morbidity and mortality in these patients, also different risk factors that are associated to malnutrition and future consequences in this type of patients are mentioned. Most of the customized formulas aimed at feeding patients with chronic kidney disease are of great help to the patient, providing proteins and nutrients vital to health, considering that these formulas could beneficially improve the health of such patients. In addition, the emotional factor may play a major role in the course of treatment. It is clear that research in this area does not have enough scientific evidence to ensure the efficacy of artificial enteral nutrition, since most of the studies carried out were of very short duration and with little participation of patients who have not been followed up in a personalized way. Finally, the importance of knowing and applying enteral nutrition formulas in patients suffering from this pathology is highlighted, however, it must be accompanied by a personalized follow-up that allows making decisions of its massive use and concrete benefits.